Mathematical models of random arrangement of amino acids in the sequence - Špokas, Alvydas; Timinskas, Albertas (Lietuvos matematikos rinkinys, 2004)
Mathematical methods which estimate the arrangement of amino acids in the random sequence where analyzed here. The random sequence of amino acids can be used as a reading point for protein’s similarities. It is important to choose rapid and accurate model for imitation of composition of random sequences.